Penyuluhan Pemeliharaan Kambing Perah PE dan Pengenalan Rumput Unggul Sebagai Pakan Alternatif Di Desa Tulabolo Barat Kecamatan Suwawa Timur, Kabupaten Bone Bolango - Umbang Arif Rokhayati (Yayasan Citra Dharma Cindekia, 2026)
This community activity aims to improve farmers understanding of PE dairy goat maintenance management and the introduction of superior types of grass as forage as well as the ability of farmers in cultivating superior grass such as elephant grass, odot grass. Community service activities were carried out in January – March 2026 in west Tulabolo Village, East Suwawa District, Bone Bolango Regency. The activity method was carried out in the form of counseling including lectures, discussions containing material on dairy goat maintenance management and the introduction of superior grass as animal feed. The community service activity ran smoothy and provided benefits to farmers in Tulabolo Village, East Suwawa District, Bone Bolango Regency. Farmers better understand the maintenance management system and superior types of grass thet are good for livestock production.